Using An EC-Wide Monetary Aggregate in Stage Two of EMU - Kenen, Peter (IMF Working Papers; Working Paper ;, 1992)
This paper looks at whether the aggregate ERM money supply has been a useful predictor of short-term changes in inflation and growth, and long-term trends in price levels among the core ERM countries. The evidence suggests that over the period since 1987, when there have been no realignments, the ERM money supply performs at least as well, and arguably better, than the individual national aggregates in predicting nominal aggregates such as inflation and the price level, while neither money supply is a good predictor of real activity.